(3QhM GdQhM ajeG MOK HYO GdeGFI GdJGSYI ef GdaJf hGdaJhMs - (3YjSi Hf dWa Gddg Hf GdeWgQ Hf jMji TQa GdOjf , GHf GdeWgQ,J (B1048 (3g` s
(3ChdgG (B:s
(3hONdJ SfI SJ hSJjf hJSYeGFI s
(3BNQgG (B:s
(3HYO PcQ SfI (B1029(3g` (B" (3hEdi gfG GfJgi GdLRA GdKGfi ef QhM GdQhM hgh GdbGOQ Cf jHdZfi ceGd GdKGdK hGdQGHY s
(3GdLR AGdKGfi ef GdfSNI faSgGs
(3HgG fXGe GdJYbjHIs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B106 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B30s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs